The Comparison of Oncologic Outcomes between Open and Laparoscopic Radical Nephroureterectomy for the Treatment of Upper Tract Urothelial Carcinoma: A Korean Multicenter Collaborative Study - Kim, Tae Heon; Hong, Bumsik; Seo, Ho Kyung; Kang, Seok Ho; Ku, Ja Hyeon; Jeong, Byong Chang (Cancer research and treatment, 2019)
We compared oncologic outcomes of patients with upper tract urothelial carcinoma (UTUC) who underwent open nephroureterectomy (ONU) or laparoscopic nephroureterectomy (LNU). Consecutive cases of ONU and LNU between 2000 and 2012 at five participating institutions were included in this retrospective analysis. Clinical characteristics and pathologic outcomes were compared between the two surgical approaches. The influence of the type of surgical approach on intravesical recurrence-free survival (IVRFS), progression-free survival (PFS), cancer-specific survival (CSS), and overall survival (OS) was analyzed using the Kaplan-Meier method and differences were assessed with the log-rank test. Predictors of IVRFS, PFS, CSS, and OS were also analyzed with a multivariable Cox regression model. A total of 1,521 patients with UTUC were eligible for the present study (ONU, 906; LNU, 615). The estimated 5-year IVRFS (57.8 vs. 51.0%, p=0.010), CSS (80.4 vs. 76.4%, p=0.032), and OS (75.8 vs. 71.4%, p=0.026) rates were significantly different between the two groups in favor of LNU. Moreover, in patients with locally advanced disease (pT3/pT4), the LNU group showed better 5-year IVRFS (62.9 vs. 54.1%, p=0.038), CSS (64.3 vs. 56.9%, p=0.022), and OS (60.4 vs. 53.1%, p=0.018) rates than the ONU group. Multivariable Cox regression analyses showed that type of surgical approach was independently associated with IVRFS, but was not related to PFS, CSS, and OS. Our findings indicate that LNU provided better oncologic control of IVRFS, CSS, and OS compared with ONU for the management of patients with UTUC.